1985
DOI: 10.1002/jcp.1041220114
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid analogs while inducing heat shock proteins sensitize CHO cells to thermal damage

Abstract: Amino acid analogs have been shown to induce heat shock proteins (HSPs). We have examined the effect of these analogs on the thermal sensitivity of Chinese hamster fibroblasts (HA-1) and their stable heat-resistant variants. We found that exposure of HA-1 cells and their heat-resistant variants to canavanine or L-azetidine-2-carboxylic acid cause enhanced synthesis of the three major mammalian HSPs (molecular weight 70,000, 87,000, and 110,000 kd). Although the synthesis of HSPs was increased, the analogs did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 23 publications
6
44
0
2
Order By: Relevance
“…HSP70 is the most prominent protein induced by a variety of stress conditions in all cells investigated (Schlesinger, 1990;Pelham, 1990 (Li & Laszlo, 1985;Riabowol et al, 1988;Johnston & Kucey, 1988). Most recently, it has been shown that cells transfected with hsp70 governed by a constitutive promoter were more resistant to heat-shock, directly supporting the above notion (Angelidis et al, 1991;Li et al, 1991).…”
Section: Discussionmentioning
confidence: 86%
“…HSP70 is the most prominent protein induced by a variety of stress conditions in all cells investigated (Schlesinger, 1990;Pelham, 1990 (Li & Laszlo, 1985;Riabowol et al, 1988;Johnston & Kucey, 1988). Most recently, it has been shown that cells transfected with hsp70 governed by a constitutive promoter were more resistant to heat-shock, directly supporting the above notion (Angelidis et al, 1991;Li et al, 1991).…”
Section: Discussionmentioning
confidence: 86%
“…(ii) Pretreatment of the cells with sodium arsenite, removal of the metal, and recovery of the cells for 12 h caused most of the 28-kDa protein to remain within the detergent soluble phase after a heat shock treatment. (iii) Pretreatment of the cells with an amino acid analog of proline, azetidine, thereby resulting in the production of nonfunctional HSPs (20,33,39,56), and subsequent heat shock treatment resulted in the protein fractionating within the insoluble pellet, similar to results with the nontolerant cells. However, pretreatment with the analog and then removal of the drug, thereby allowing for production of functional stress proteins (20,39,56), now resulted in significantly more of the protein remaining within the soluble phase after heat shock treatment, similar to the effect with thermotolerant cells.…”
Section: Discussionmentioning
confidence: 97%
“…일반적으로 동물 세포 나 기관이 스트레스에 노출되면 대부분의 다른 단백질은 합 성이 억제되나, HSPs는 특이적으로 빠르게 합성된다고 한다. HSPs는 세포의 항상성에 중요한 역할을 하며, 고온이나 중금 속, 산화 스트레스 등에 의해 발현량이 증가하며, 원핵․진핵 생물의 모든 세포에서 검출된다 (Craig, 1985;Li and Laszlo, 1985;Lindquist, 1986;Lindquist and Craig, 1988;Young et al, 2001;Powers and Workman, 2007). 특히, HSP-70은 스 트레스에 가장 민감하게 반응하는 열 스트레스 단백질로 닭 에 있어서도 제한급여, 수송, 격리와 같은 스트레스원에 노 출되면 HSP-70 유전자의 발현이 현저하게 상승한다고 한다 (Kamboh et al, 2013;Zulkifli et al, 2014).…”
unclassified